Breads, grains and rice - Thomas, Ann, 1953- (South Melbourne : Macmillan Education Australia, 1998)
A simple introduction to breads, grains and rice which looks at how they are grown, processed and used in food products, and why they are important in a balanced diet. Suggested level: junior, primary.
Includes index.
Keywords: Food -- Juvenile literature; Bread -- Juvenile literature; Grain -- Juvenile literature; Rice -- Juvenile literature; Bread; Grain; Rice